2013
DOI: 10.2465/jmps.130212
|View full text |Cite
|
Sign up to set email alerts
|

Local structure of iron in tektites and natural glass: An insight through X-ray absorption fine structure spectroscopy

Abstract: The local structure of iron in tektites from six strewn fields, and impact -and non -impact -related glass were studied using the Fe K -edge X -ray absorption near edge structure (XANES) and extended X -ray absorption fine structure (EXAFS) techniques, in order to obtain quantitative data on Fe -O bond length and Fe coordination number. X -ray absorption fine structure (XAFS) spectra and Fe -O bonds in standard minerals such as hematite, fayalite, and magnetite were compared. The degree of oxidation was measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…Overall, these results confirm that Fe in the melt glasses is predominantly 4-coordinate Fe(II). The bond lengths observed for the melt glasses and tektite are near the endpoints of the previously reported range for tektites collected from various strewnfields [52,63].…”
supporting
confidence: 71%
See 1 more Smart Citation
“…Overall, these results confirm that Fe in the melt glasses is predominantly 4-coordinate Fe(II). The bond lengths observed for the melt glasses and tektite are near the endpoints of the previously reported range for tektites collected from various strewnfields [52,63].…”
supporting
confidence: 71%
“…4, the k-space Fe K-edge EXAFS collected from the soil and glass samples are shown with spectra collected from staurolite, containing 4-coordinate Fe(II) [55]; grandidierite, containing approximately 90% 5-coordinate Fe(II) and 10% Fe(III) [60]; and a tektite from the Australasian strewnfield [61]. Tektites have been proposed as naturally occurring analogs to nuclear melt glass [56,57], and are reported to predominantly contain Fe(II) in distorted tetrahedral coordination [43,62,63]. Table III show EXAFS fitting results.…”
mentioning
confidence: 99%
“…A condition such as high-temperature melt was quenched rapidly in the space with little oxygen pressure condition may be supposed. This consideration is consistent with the result of Wang et al (2013): since tektite glasses are formed in the space under low oxidation conditions, iron ions in tektite has abnormally high ratio of Fe 2+ /(Fe…”
Section: Xanes Spectra Of Natural Glasses and K-t Boundary Clayssupporting
confidence: 79%
“…XAS (X-ray Absorption Spectroscopy) studies of glass materials are numerously reported in the material sciences literature, covering such disparate applications as the investigation of historic artifacts (e.g., [6]) or geological specimen (e.g., [7]), characterization of optical glasses for solid state lasers (e.g., [8]) or the encapsulation of radiotoxic residues from nuclear fuel reprocessing (notably the work of McKeown et al [9][10][11][12][13][14][15][16]). These studies benefit from the ability of X-ray Absorption Fine Structure (XAFS) measurements to provide direct chemical speciation (e.g., determination of oxidation states and coordination geometries) through analysis of the Xray Absorption Near Edge Structure (XANES) -without the need for any sample pretreatment -while the Extended X-ray Absorption Fine Structure (EXAFS) reveals structural details on the local coordination environments (bond lengths, neighboring atom types) of glass matrix constituents -unlike standard X-ray Diffraction (XRD) analysis, which is severely hampered by the amorphous nature of elemental networks in glassy materials lacking any long range order.…”
Section: Introductionmentioning
confidence: 99%